If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2u + -5)(6 + u) = 0 Reorder the terms: (-5 + 2u)(6 + u) = 0 Multiply (-5 + 2u) * (6 + u) (-5(6 + u) + 2u * (6 + u)) = 0 ((6 * -5 + u * -5) + 2u * (6 + u)) = 0 ((-30 + -5u) + 2u * (6 + u)) = 0 (-30 + -5u + (6 * 2u + u * 2u)) = 0 (-30 + -5u + (12u + 2u2)) = 0 Combine like terms: -5u + 12u = 7u (-30 + 7u + 2u2) = 0 Solving -30 + 7u + 2u2 = 0 Solving for variable 'u'. Factor a trinomial. (-6 + -1u)(5 + -2u) = 0Subproblem 1
Set the factor '(-6 + -1u)' equal to zero and attempt to solve: Simplifying -6 + -1u = 0 Solving -6 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1u = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1u = 0 + 6 -1u = 0 + 6 Combine like terms: 0 + 6 = 6 -1u = 6 Divide each side by '-1'. u = -6 Simplifying u = -6Subproblem 2
Set the factor '(5 + -2u)' equal to zero and attempt to solve: Simplifying 5 + -2u = 0 Solving 5 + -2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2u = 0 + -5 -2u = 0 + -5 Combine like terms: 0 + -5 = -5 -2u = -5 Divide each side by '-2'. u = 2.5 Simplifying u = 2.5Solution
u = {-6, 2.5}
| x+24+4x=-22-4x-26 | | -1/4x=21/4 | | (15x+7y)+(48x+25y)= | | 7-3(x-1)=2x | | an=-6n+10 | | x+1/2=0.98 | | -16t^2+20t+4=0 | | z/10-4=10 | | -1/X=0 | | a^2+21a-540=0 | | (45x+54y)+(-2x+33y)= | | 4x-2/2=-3 | | -u/12=12 | | -7+|-5|= | | x-0.08x=1700 | | 18+6x-12=-8-4x+9x | | (9x^(1/2))^2 | | 14z-7/7 | | 2*B+3*A=5 | | (14x-27y)+(32x+65y)= | | 5/6x^2*3/6x^2 | | 3(x-4)=12x-4-9x | | 2x^3-15x^2+24x+12=0 | | (50x-8y)+(32x+37y)= | | 24+x=-18 | | -3x^2-12x+1=0 | | 28=w(2w-1) | | (x-2)(x+4)=14 | | x^2+x-36= | | 12c+5=c+31 | | 35x+-14=36x+-6 | | -18=x+20 |